COMPARED ANALYSIS OF THE SAME STIMULUS FROM THE MACEDONIAN ASSOCIATIVE DICTIONARY WITH OTHER ASSOCIATIVE DICTIONARY - Sokolova, Marija (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
The benefits of creating an associative dictionary are vast. One of them is the possibility to make a comparative analysis between associations of associative dictionaries among different nations, i.e. languages. Thus, it is possible to discover the specificities (similarities and differences) among people. When making such comparative analyzes, the best results are achieved if the analysis is done in associative dictionaries of people (states) whose languages are similar or derived from the same language group, for example, a comparison of the associations among Slavic people. However, here we do not mean only the common SLAR - Slavonic associative vocabulary, but also the individual associative dictionaries of Slavic people.